The “Noël” in French Baroque Organ Music - Tchebourkina, Marina N. (Music Scholarship / Problemy Muzykal'noj Nauki, 2012)
This article is devoted to analysis of the genre of the Noël in French Baroque organ music. The author presents the musical sources of this genre and traces its evolution. The conclusion is made, based upon the analysis of the particularities of this style, as well as the documentary evidence of the time, of the secularization of this religious genre and an increase of its manifestation in public concerts towards the end of the 18th century. Keywords: Noël, Organ, France, Baroque, Daquin, Balbastre, Beauvarlet-Charpentier